2014
DOI: 10.1111/1471-0528.12612
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial job strain and risk of congenital malformations in offspring—a Danish National cohort study

Abstract: Objective To investigate if maternal exposure to psychosocial job strain at work (high demands and low control) measured by questionnaire early in pregnancy (median week 15) is associated with malformations in the offspring.Design Population-based cohort study.Setting The Danish National Birth Cohort.Population A cohort of 60 386 singleton children with full information on mother's occupational status, exposure to psychosocial job strain and all covariates during pregnancy.Methods Logistic regression analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…In another study, no relationship was found between psychological stresses of working mothers until 15 weeks (even with age and type of job controlled) and infant’s skeletal and cardiovascular abnormalities ( Larsen et al, 2014 ; A. D. Larsen et al, 2013 ). Maternal exposure to allergens can afflict their children with asthma by the age of 7 years, disregarding child’s gender ( Bajeux et al, 2014 ; Christensen et al, 2013 ).…”
Section: Discussionmentioning
confidence: 93%
“…In another study, no relationship was found between psychological stresses of working mothers until 15 weeks (even with age and type of job controlled) and infant’s skeletal and cardiovascular abnormalities ( Larsen et al, 2014 ; A. D. Larsen et al, 2013 ). Maternal exposure to allergens can afflict their children with asthma by the age of 7 years, disregarding child’s gender ( Bajeux et al, 2014 ; Christensen et al, 2013 ).…”
Section: Discussionmentioning
confidence: 93%
“…The risk of developing complications is not related to work activity or to the psychosocial stress of work. 120 However, demands and working conditions should be evaluated individually in women with limiting heart disease or obstetric situations, such as preeclampsia and IUGR. Changes or adaptations in work activities, reduced stress at work, or increased rest and relaxation periods are often beneficial measures, especially if the condition worsens or limiting symptoms appear.…”
Section: Professional Activitymentioning
confidence: 99%
“…As Lee et al ( 4 ) point out, the gestational period brings about a series of physiological, physical, hormonal, and emotional changes that facilitate adequate foetal development and that in certain cases, especially when the pregnancy is advanced, there may be certain conditions in the working environment that limit the pregnant’s ability to work. It is precisely this line that has been the focus of some studies such as the one by Larsen et al ( 5 ) or by Katz ( 6 ), among others, whose research has aimed at analysing the risks existing in the workplace and how these can affect the normal development of pregnancy. In fact, certain working conditions such as heavy physical work, prolonged standing during the working day, carrying loads, among others, have been related to higher rates of adverse effects during pregnancy ( 7 ), as well as specific risks such as those derived from chemical products, thus requiring careful risk assessment ( 8 ).…”
Section: Introductionmentioning
confidence: 99%